Father absence and age at menarche: A test of four evolutionary models - Hoier, Sabine (Human nature (Hawthorne, N.Y.), 2003)
Life history data, attractiveness ratings of male photographs, and attitudes towards partnership and child-rearing of 321 women were used to test four evolutionary models (quantitative reproductive strategy, male short-age, polygyny indication, and maternal reproductive interests) which attempt to explain the influence of family composition on reproductive strategies. Links between early menarche and other markers of reproductive strategy were investigated. Childhood stress and absence of a father figure, whether genetically related or not, were found to have accelerated menarche whereas having younger siblings decelerated it. Early menarche was associated with attractiveness ratings, the number of partners desired for the immediate future, and the early onset of intimate relationships. It was not linked with sociosexual orientation, mate choice criteria, and investment in the subjects' own children, but these three markers were interrelated. The implications of the findings for the four evolutionary models are discussed.